2022
DOI: 10.48550/arxiv.2205.07515
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

There is no universal acceleration scale in galaxies

Abstract: Recently, many studies seem to reveal the existence of some correlations between dark matter and baryonic matter. In particular, the unexpected tight Radial Acceleration Relation (RAR) discovered in rotating galaxies has caught much attention. The RAR suggests the existence of a universal and fundamental acceleration scale in galaxies, which seems to challenge the ΛCDM model and favour some modified gravity theories. A large debate about whether RAR is compatible with the ΛCDM model has arisen. Here, by analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…However, the Bayesian techniques has been critised by Li et al (2021) who cautioned the use of degenerated parameters and demonstrated that G, the constant of gravitation, may turn out different from galaxy to galaxy. Recently, Chan et al (2022) found for a sample of MaNGA galaxies the acceleration scale by roughly a factor 1.5 higher than that for spiral galaxies. They boldly conclude that there is no universal acceleration among galaxies and take that as a falsification for MOND.…”
Section: Bayesian Fits To Rotation Curvesmentioning
confidence: 90%
“…However, the Bayesian techniques has been critised by Li et al (2021) who cautioned the use of degenerated parameters and demonstrated that G, the constant of gravitation, may turn out different from galaxy to galaxy. Recently, Chan et al (2022) found for a sample of MaNGA galaxies the acceleration scale by roughly a factor 1.5 higher than that for spiral galaxies. They boldly conclude that there is no universal acceleration among galaxies and take that as a falsification for MOND.…”
Section: Bayesian Fits To Rotation Curvesmentioning
confidence: 90%